Methods And Techniques Of Teaching Russian Language - Abduraxmanova Dilbarxon Abdullaxamidovna (Genius Publishing Group, 2024)
The proposed material will help teachers to properly organize their activities not only in preparation for practical classes in the subject, but also during teaching practice in the Russian language. The article is addressed to philologists, teachers of Russian language methods, practical teachers , as well as literature teachers. The proposed material will be useful and interesting to everyone who seeks to diversify teaching methods and mastering the course of methods of teaching the Russian language, work on the subject. The material is addressed to the possibilities of developing analytical thinking, to the prospects for solving innovative problems of modern teaching of the Russian language. In addition, classifications of teaching principles and methods are proposed that allow the teacher to see the design of the educational process in perspective, and those used in modern educational institutions are analyzed.
Keywords: learning models; types of learning; teaching methods